2014
DOI: 10.1155/2014/370403
|View full text |Cite
|
Sign up to set email alerts
|

FitKids360: Design, Conduct, and Outcomes of a Stage 2 Pediatric Obesity Program

Abstract: This paper describes FitKids360, a stage 2 pediatric weight management program. FitKids360 is a physician-referred, multicomponent, low-cost healthy lifestyle program for overweight and obese youth 5–16 years of age and their families. FitKids360 provides an evidence-based approach to the treatment of pediatric overweight by targeting patients' physical activity, screen time, and dietary behaviors using a family-centered approach. The intervention begins with a two-hour orientation and assessment period follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…A summary of all included studies is shown in Table 1. Three articles were published in 2007 [13][14][15], two in 2009 [16,17], one in 2010 [11], one in 2011 [18], one in 2013 [19] and one in 2014 [20]. Most of the studies included in the review were interventions conducted in the US, with one study conducted in Australia [15], and one study conducted in Italy [14].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A summary of all included studies is shown in Table 1. Three articles were published in 2007 [13][14][15], two in 2009 [16,17], one in 2010 [11], one in 2011 [18], one in 2013 [19] and one in 2014 [20]. Most of the studies included in the review were interventions conducted in the US, with one study conducted in Australia [15], and one study conducted in Italy [14].…”
Section: Resultsmentioning
confidence: 99%
“…In three studies, children with BMI of ≥85th percentile were included in the interventions [16,19,20]. The study by Kwapiszewski et al had additional inclusion criteria of children being overweight (BMI > 85th percentile and <95th percentile), obese (BMI > 95th percentile) or at risk for obesity, which considers age as well as corresponding BMI [18].…”
Section: Intervention Participantsmentioning
confidence: 99%
See 3 more Smart Citations